PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPA SEKOLAH DASAR - Munir, Muhammad; Sholehah, Hijriati (LP2M STAI Darul Kamal NW Kembang Kerang, 2022)
Abstract The demonstration method is a show about the process of the occurrence of an event or object to the appearance of exemplary behavior so that students can know and understand it in real or imitation. In other words, the demonstration method is a practical method that is carried out by demonstrating or demonstrating to students related to the material or discussion when learning takes place. This study uses library research, using a qualitative descriptive analysis. The data collected is in the form of documents, namely articles or theses of the past five years. Based on the results of document analysis, that the Application of the Demonstration Method to improve learning outcomes in elementary school science subjects is very suitable to be applied in elementary schools